1979
DOI: 10.1002/aic.690250302
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the dynamic behavior of deep bed filters

Abstract: A simulation procedure for predicting the dynamic behavior of a deep bed filter over the entire practicable range of filter operation is developed. The method is based on synthesizing available quantitative results relating to filtration, and to porous media flows, within an overall framework which views the process to consist of two principal stages dominated by appropriate limiting deposition modes. Evaluation of the results through comparison with available data indicates, to the extent the nature of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(60 citation statements)
references
References 20 publications
0
58
1
1
Order By: Relevance
“…This assumption has been widely used in the clogging models presented in the introduction [9,13]. To validate it, carbon nanoparticles deposited under predominant Brownian diffusion on a line of magnetic beads were observed under a microscope.…”
Section: Presentation Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption has been widely used in the clogging models presented in the introduction [9,13]. To validate it, carbon nanoparticles deposited under predominant Brownian diffusion on a line of magnetic beads were observed under a microscope.…”
Section: Presentation Of the Modelmentioning
confidence: 99%
“…To overcome these issues, Tien et al [9] developed a hybrid model for the liquid filtration of 6-µm-diameter particles, by splitting the deposition process into two steps. Thus, the deposit was initially considered to form a smooth layer over the grains, and then to gradually obstruct the pore space causing a decrease in the number of pores available to induce flow.…”
Section: Introductionmentioning
confidence: 99%
“…The physical simulation techniques and computer-based mathematical models [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] were used in aluminum industry to have a fairly good understanding of the thermal and hydrodynamic aspects of the filtration process during the last two decades. However, the experimental studies were carried out mostly with water since it is very difficult and costly to carry out aluminum filtration studies in the laboratory.…”
Section: The Statement Of the Problemmentioning
confidence: 99%
“…It is stated that particulate type and size, fluid approach velocity, temperature and media characteristics are important parameters which determine the relative dominance of each force mentioned above. However, studies [18,21,[91][92][93] conducted on the description of potential capture mechanisms in aqueous systems indicated that pressure/Van der Waals forces/double layer forces are responsible for particle attachment.…”
Section: Inclusions In Molten Aluminum Alloysmentioning
confidence: 99%
“…The problem of removing small particles from gases or liquids has become increasingly important, and many theoretical and experimental studies have been conducted (Yeh and Liu, 1974;Gebhart et al, 1973;Paretsky et al, 1971;Liu and Wang, 1997;Tien et al, 1979;Lee and Gieseke, 1979). The motion and capture of particles by an ensemble of fluid spheres can be applied directly to the problem of wet scrubbers or to the capture of particles by bubbles in a water pool.…”
Section: Introductionmentioning
confidence: 99%